Przekształć wyrażenia korzystając z odpowiedniego wzoru skróconego mnożenia :
a) (x+3) do kwadratu
b)(x+5)do kwadratu
c)(4+x)do kwadratu
d)(10+x)do kwadratu
e) (x+7)do kwadratu

k) (x-6)do kwadratu
l) (x-4)do kwadratu
m) (3-x)do kwadratu
n) (9-x)do kwadratu
o) (x-20)do kwadratu

bardzo proszę o odp.

2

Odpowiedzi

2010-02-01T19:35:10+01:00

a) (x+3)²=x²+2×x×3+3²=x²+6x+9
b)(x+5)²=x²+2×x×5+5²=x²+10x+25
c)(4+x)²=4²+2×4×x+x²=16+8x+x²
d)(10+x)²=10²+2×10×x+x²=100+20x+x²
e) (x+7)²=x²+2×x×7+7²=x²+14x+49

k) (x-6)²=x²-2×x×6+6²=x²-12x+36
l) (x-4)²=x²-2×x×4+4²=x²-8x+16
m) (3-x)²=3²-2×3×x+x²=9-6x+x²
n) (9-x)²=9²-2×9×x+x²=81-18x+x²
o) (x-20)²=x²-2×x×20+20²=x²-40x+400
2010-02-01T19:38:10+01:00
(a+b)²=a²+b²+2ab

a)x²+3²+2×3x
x²+9+6x

b) x²+5²+2×5x
x²+25+10x

c) 4²+x²+2×4x
16+x²+8x

d) 10²+x²+2×10x
100+x²+20x

e)x²+7²+2×7x
x²+49+14x


(a-b)²=a²+b²-2ab

k) x²+6²-2×6x
x²+36-12x

l) x²+4²-2×4x
x²+16-8x

m) 3²+x²-2×3x
9+x²-6x

n) 9²+x²-2×9x
81+x²-18x

o) x²+20²-2×20x
x²+400-40x
1 5 1